Instructions not included : how a team of women coded the future - Brown, Tami Lewis; Dunn, Debbie Loren (Disney/Hyperion, 2019)
"The nonfiction story of a team of women innovators, Jean Jennings Bartik, Kay McNulty Mauchly, and Betty Snyder Holberton, who programmed early computer ENIAC (Electronic Numerical Integrator and Computer)"--